Hubungan Faktor Sosiodemografi dengan Penggunaan Intrauterine Device (IUD) - Ana Fitrotul Laili (Jurnal Ilmiah Kesehatan, 2022)
Contraception in family planning is a practice that could help an individual or couples in their fertile age to plan and regulate birth. However, the 2017 Indonesian. Ngadiluwih sub-district is one of the regions with the lowest prevalence level of modern contraception in Kediri Regency, reaching 57,71% point with IUD usage of only 10,42%. The purpose of this research is to analyze the relation between sociodemographic factors and the IUD usage in Public Health Center of Wonorejo, Ngadiluwih sub-districts in 2021. This study uses observational analytic method with study design of case control. This research uses secondary data based on acceptor's medical record in Wonorejo Public Health Center from January to December 2021. The population found in this research recorded 192 acceptors. The sample size is obtained from simple random sampling and it is found that there are 56 cases and 56 controls. The data is analyzed using univariate and bivariate analysis with chi-square test that has significance of (α=0,05). The research result is obtained through 3 sociodemographic variables (p<0,05) with age, number of living children, and the age of last children. Sociodemograhic factors which are age, the number of living children and the age of last children acceptor, have a significant relation with the usage of IUD in Wonorejo Public Health Center in 2021. This research findings reinforce the needs of sociodemographic factors influence especially those of age, the number of living children and the age of last children to increase utilization of IUD service.